Sistema eletrônico de registros públicos: extrajudicialização e desmaterialização do acesso à justiça na atividade notarial e registral no contexto do ativismo judicial-administrativo, nos termos da Lei nº 14.382, de 27 de junho de 2022 - MORAIS, Salomão Saraiva de (2025)
This study examines judicial-administrative activism in Brazil, with a particular focus on the Judiciary’s normative intervention in the Extrajudicial Justice System following the establishment of the Sistema Eletrônico de Registros Públicos (SERP) by Law No. 14,382/2022. Its central object is the impact of this form of activism on extrajudicial registry practice, considering its philosophical, historical, and technological underpinnings, its effects on the separation of powers, and the constitutional limits on the Judiciary’s normative role. We advance the hypothesis that Law No. 14,382/2022 amplifies judicial-administrative activism - especially within notarial and registry contexts – by promoting the extrajudicialization and dematerialization of access to justice. Concurrently, this phenomenon exposes interinstitutional tensions by challenging strict legality and the balance among the Republic’s Powers, particularly through the issuance of primary-normative administrative acts by bodies such as the Conselho Nacional de Justiça (CNJ) and regional corrigedorias. The core question guiding this inquiry is whether the advent of SERP creates new opportunities for judicial-administrative activism by the Judiciary. Accordingly, the general objective is to analyze SERP as an expression of such activism and to understand its effects on the normative reorganization of the Extrajudicial Justice System. The specific objectives are to: (i) conceptualize and delimit judicial-administrative activism in the context of SERP; (ii) investigate its philosophical, historical, and technological foundations; and (iii) analyze the normative activity of judicial corregedorias, with particular attention to activist administrative stances adopted by the Corregedoria Nacional de Justiça (CN/CNJ) and the Corregedoria Geral do Foro Extrajudicial do Tribunal de Justiça do Maranhão (COGEX). The findings indicate that judicial- administrative activism has been filling legislative gaps, enhancing the CNJ’s leadership in implementing SERP, with positive effects on the modernization and debureaucratization of registry services. However, this has come at the expense of strengthening the Judiciary’s autonomy vis-à-vis the other Republican Powers, revealing risks such as the CNJ’s normative centralization, the weakening of state corregedorias’ normative autonomy, and the exclusion of delegated registry operators and civil society from the decision-making process. This research holds social, academic, and practical relevance by proposing and elaborating the legal concept of judicial-administrative activism and contributing to the debate on the constitutional limits of the Judiciary’s normative function in an era of digital transformation. It thereby provides an instrumental foundation for enhancing the institutions of Brazil’s Justice System. Methodologically, the study adopts an inductive approach, employing historical-legal and legal- comprehensive methods, alongside bibliographic and document-based research techniques.